2012
DOI: 10.1021/ja2106724
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Surface Diffusion of Tripodal Binding Motifs on Graphene Using Scanning Electrochemical Microscopy

Abstract: The surface diffusion of a cobalt bis-terpyridine, Co(tpy)(2)-containing tripodal compound (1·2PF(6)), designed to noncovalently adsorb to graphene through three pyrene moieties, has been studied by scanning electrochemical microscopy (SECM) on single-layer graphene (SLG). An initial boundary approach was designed in which picoliter droplets (radii ~15-50 μm) of the tripodal compound were deposited on an SLG electrode, yielding microspots in which a monolayer of the tripodal molecules is initially confined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 103 publications
1
67
0
Order By: Relevance
“…This is quite different from the present study of us. In addition, studies in literature demonstrated that pyrene‐derivatives could be efficiently attached on graphene via π – π interactions . These studies also provide additional evidence for our success in chiral functionalization of graphene, as reported above.…”
Section: Resultssupporting
confidence: 71%
“…This is quite different from the present study of us. In addition, studies in literature demonstrated that pyrene‐derivatives could be efficiently attached on graphene via π – π interactions . These studies also provide additional evidence for our success in chiral functionalization of graphene, as reported above.…”
Section: Resultssupporting
confidence: 71%
“…On substrate electrodes even a few radii larger than the SECM tip, open-circuit SECM positive feedback makes it technically challenging to discern between the SI-SECM signal and the background. However, a large subset of surface explorations can proceed on active semiconducting or kineticallylimited substrates that do not display open-circuit feedback [26,[47][48][49]. Here, we show this concept for a lightly n-doped sample of strontium titanate which generates adsorbed oxygenated O(H)Á ads intermediates during the photoassisted oxidation of water.…”
Section: Introductionmentioning
confidence: 89%
“…Often, kinetic theory can help to elucidate reaction mechanisms [10,16,17], but direct chemical information improves these models [18], especially when diverse chemical intermediates are possible [19]. In particular, SECM offers a unique opportunity to correlate the spatially-resolved information about reactivity at specific photo catalytic sites [20][21][22][23][24] to the surface coverage of reacting species [25,26] with potential applications at the nano-scale [27,28]. This work introduces the basic considerations towards applying redox micro-and nano-titrations via transient SECM [29,30] for the local quantification of reactive intermediates at a substrate of unconstrained dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Glassy carbon (GC), boron doped diamond and graphite have long received attention for electroanalytical and electrocatalytic measurements, [5][6][7][8][9][10][11] and, more recently, carbon nanotubes and graphene have generated considerable interest. [12][13][14][15][16][17] However, despite well-defined bulk properties and structure, carbon materials can possess rather complex surface chemistry that may substantially impact the resulting electrochemistry. 6 Indeed, the range of functional groups present at different carbon electrode/electrolyte interfaces is yet to be fully understood 9 and is significantly impacted by electrode preparation.…”
Section: Introductionmentioning
confidence: 99%